2003
DOI: 10.1002/adma.200300386
|View full text |Cite
|
Sign up to set email alerts
|

Materials Aspects of Photonic Crystals

Abstract: Photonics, the technology of photons (as electronics is the technology of electrons), promises to be the new century's driving force in the advancement of, mainly but not only, information technology, such as communications and computing. This technology was initiated with the advent of lasers and optical fibers that, for various reasons, embody the best choice of source and channel of the information carrier: the photon. If the parallel with electronics is to be further pursued, one soon realizes that many mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
537
0
3

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 914 publications
(555 citation statements)
references
References 238 publications
3
537
0
3
Order By: Relevance
“…However, especially surfactant-free emulsion polymerization is priced for the high monodispersity [29,183] of the resulting latex particles. These find applications where high precision colloidal crystals are needed, most prominently in the fields of photonics, [184][185] phononics, [186][187] and lithography. [5,136,188] As the symmetry and order of the nanoparticles arrays to be produced from the metal-complex containing colloids crucially depends on the uniformity of the colloids, surfactant-free emulsion polymerization was applied to incorporate different metal complexes in order to produce colloids with a narrow size distribution.…”
Section: Incorporation Of Metal Complexes By Emulsion Polymerizationmentioning
confidence: 99%
“…However, especially surfactant-free emulsion polymerization is priced for the high monodispersity [29,183] of the resulting latex particles. These find applications where high precision colloidal crystals are needed, most prominently in the fields of photonics, [184][185] phononics, [186][187] and lithography. [5,136,188] As the symmetry and order of the nanoparticles arrays to be produced from the metal-complex containing colloids crucially depends on the uniformity of the colloids, surfactant-free emulsion polymerization was applied to incorporate different metal complexes in order to produce colloids with a narrow size distribution.…”
Section: Incorporation Of Metal Complexes By Emulsion Polymerizationmentioning
confidence: 99%
“…Structured dielectric materials in three dimensions can exhibit photonic properties that allow control of the propagation of light [1][2][3][4][5][6][7]. For crystalline structures, a complete or incomplete photonic band gap emerges and the propagation of light is hindered or even completely suppressed over a certain range of wavelengths.…”
Section: Introductionmentioning
confidence: 99%
“…A review of PBG fabrication methods can be found in the literature. [5] The development of efficient, practical techniques amenable to the fabrication of cPBG materials operating in the visible to IR remains a vibrant area of research, with new approaches regularly being introduced in the literature. Many applications have been identified for PhCs and PBG materials, including low-threshold lasers, [3] low-loss waveguides, [6][7][8] on-chip optical circuitry, [9] and fiber optics.…”
Section: Introductionmentioning
confidence: 99%
“…A review of PBG fabrication methods can be found in the literature. [5] The development of efficient, practical techniques amenable to the fabrication of cPBG materials operating in the visible to IR remains a vibrant area of research, with new approaches regularly being introduced in the literature.…”
Section: Introductionmentioning
confidence: 99%